Micro-structures, mineralogy and geochemistry of clay size fraction (< 2 µm) of thrust zones of western Nepal Siwaliks (Karnali area) - Huyghe, Pascale; Galy, Albert; Mugnier, Jean- Louis (Journal of Nepal Geological Society, 1998)
Shear zones of the Main Dun Thrust (MDT) of the Siwaliks of western Nepal have been investigated in order to specify the deformation mechanisms and mineral transformations. The Riedel fractures and cleavage are developed. They are responsible for the scaly fabric of the fault zones and generate a "tectonic mixture" of both the Upper and Lower Siwaliks at the footwall and hangingwall of the MDT. Grain-size analysis of samples from the shear zones indicates a strong cataclastic deformation. Clay mineralogy varies significantly within the shear zone. However, the smectites abundance is higher in the shear zone than in the Upper and Lower Siwaliks and may exceed 40% of the <2 µm clay fraction. The isotopic oxygen composition of clay fractions in the shear zone gives δ18O of smectites that implies neoformation. The temperature of smectite neoformation is 40 to 60°C higher than pedogenic smectites present in the borders. δD of fluid inclusion of calcite associated to deformation show values consistent with water similar to the actual surface water and δ18O of mineral implies temperature of crystallisation around 50°C. These low temperatures are in good agreement with the precipitation of smectites and kaolinites. Fluids sampled in hot springs of the Siwaliks of western Nepal have a meteoric origin with respect to the stable isotopes but are enriched in Na and depleted in K. The chemistry suggests the partial dissolution of feldspar and neoformation of smectites induced by fluid circulation. It is presumed that shearing and crushing take place during seismic slip increasing the exchanging mineral surfaces whereas mineralogical reactions occur during interseismic periods.